A DIFFICULT DIAGNOSIS AND CHALLENGING MANAGEMENT OF AN AGGRESSIVE CASE OF AQUAPORIN 4 NEGATIVE NMOSD - Khan, Amna; Zahoor, Warda; Zehra, Taskeen; Ullah, Zafar; Nabeel Muzaffar Syed (Journal of Ayub Medical College Abbottabad, 2023)
Neuromyelitis optica spectrum disorders can be challenging to diagnose and manage. There is considerable potential long term morbidity but this can be avoided by appropriate treatment. Here we present one such case that is interesting as well as instructive.